1995
DOI: 10.1016/0020-7292(94)02236-4
|View full text |Cite
|
Sign up to set email alerts
|

Ureaplasma urealyticum cervical colonization as a marker for pregnancy complications

Abstract: Cervical colonization with Uu when associated with elevated titers of antibodies to Uu, may serve as a marker for the identification of a subpopulation of women who are at high risk for the development of pregnancy complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Similarly, it was concluded by Wenstrom et al (4) that high levels of IL-6 at genetic amniocentesis can predict subsequent pregnancy loss. The association of Ureaplasma urealyticum with pregnancy complications was previously reported by several groups including ours (6)(7)(8)17). Moreover, Horowitz et al (18) previously showed that the three women with U.urealyticum infection also had high titers of anti-ureaplasma antibodies.…”
Section: Discussionsupporting
confidence: 68%
“…Similarly, it was concluded by Wenstrom et al (4) that high levels of IL-6 at genetic amniocentesis can predict subsequent pregnancy loss. The association of Ureaplasma urealyticum with pregnancy complications was previously reported by several groups including ours (6)(7)(8)17). Moreover, Horowitz et al (18) previously showed that the three women with U.urealyticum infection also had high titers of anti-ureaplasma antibodies.…”
Section: Discussionsupporting
confidence: 68%
“…Conflicting associations between mollicutes and preterm birth have had a long history, not only related to population tested, but also to testing itself (culture vs PCR) (5,7,8,9,10,11,12,16,20,21,22,23,24,25,26). We used PCR probes that can separate M hominis , M genitalium , and U parvum from U urealyticum (18).…”
Section: Discussionmentioning
confidence: 99%
“…Some urogenital mollicutes ( Mycoplasma and Ureaplasma species, which are bacteria without cell walls) have been associated by culture with preterm birth in many (7,8,9,10), but not all (5,11,12), studies. Causality for preterm birth or labor is plausible because mollicutes possess adhesion molecules that interact with toll-like receptors and stimulate secretion of pro-inflammatory cytokines IL2, IL4, and IL6 (2,4,5,6,12,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…can be isolated from endometrial tissue of healthy, nonpregnant women, indicating that they may be present at the time of implantation and might therefore be involved in early pregnancy losses (44). Horowitz et al (122) reported that women whose cervices were culture positive for Ureaplasma spp. and who had a high level of antibody against ureaplasmas were more likely to develop pregnancy complications than women with a negative culture and absence of antibodies.…”
Section: Chorioamnionitis Spontaneous Abortion and Preterm Labormentioning
confidence: 99%